The Effect of The Environment Condition on The Strength of Fishing Net - Azhar, Ahmad FIrdaus; Siti Zaharah Kunchi Mon (Progress in Engineering Application and Technology, 2022)
The environmental condition plays a significant role to the strength of the fishing net. As it could lead the net to break during fishing. The strength of fishing nets is critical for fishing activities, since a lack of net strength can result in fish escape, ghost fishing, and economic losses. The main objective of this study is to determine the strength properties of fishing nets in different environmental conditions. The strength of the fishing nets were measured from tensile test. For sample A it will be put into light fastness machine, sample B will be soaked in a container of seawater, and sample C will be in both condition which is the sample will be soaked in the container of seawater before taken out to put into light fastness machine. Tensile test machine will be used to get the raw data for the specimen. Based on the result obtained, different environmental condition have different degradation and the elongation of the nets were dropped as the time spent in each environmental condition increased. Exposing the fishing net under environmental condition takes a toll to its tensile properties. It is concluded that the environmental condition do affect fishing net tensile properties and breaking strength.